Enviroshopping: Buy Smarter - Marie Hammer; Joan Papadi (EDIS)
This document is FCS 3158, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date: July 2002. First published: June 1991. Revised: July 2002. Written by Marie Hammer and Joan Papadi.